Ayaktan hasta memnuniyet ölçeği: ölçek geliştirme, güvenirlik ve geçerlik çalışması - Kevenk, Ahmet Uğur; Yılmaz, Fatma Kantaş (Sağlık Bilimleri Dergisi, 2021)
[Abstract Not Available]
Outpatient satisfaction scale: a study of scale development, reliability and validity
Keywords: Ayaktan hasta memnuniyeti; hasta memnuniyeti; ölçek geliştirme; sağlık yöntemi; Health management; outpatient satisfaction; patent satisfaction; scale development